ANALISIS RASIO LIKUIDITAS DAN RASIO SOLVABILITAS TERHADAP KINERJA KEUANGAN PT UNILEVER INDONESIA TBK - Rangga Bayu Putra; Putri Amelia; Qisthy Chaerunnisa; Rinda Septiani; Sunita Dasman (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
This research aims to determine the financial performance of PT Unilever Indonesia Tbk which is listed on the IDX using Liquidity Ratio and Solvency Ratio analysis. This study uses a quantitative approach. The data source used in this research is secondary data and the data collection technique in this research is documentation. The population in this study is the cosmetics industry registered on the IDX and the sampling method uses a purposive sampling technique, so the sample in this study is PT Unilever Indonesia Tbk for the period 2003 to 2022. The results of this study show that the Liquidity Ratio analysis is measured by current ratio at PT Unilever Tbk for the period 2003 to 2022. Partially, the Liquidity Ratio has no significant effect on PT's Financial Performance. Unilever Indonesia Tbk. And analysis of the Solvency Ratio as measured by the Debt to Assets Ratio at PT Unilever Indonesia Tbk for the period 2003 to 2022, partially the Solvency Ratio has no significant effect on PT's Financial Performance. Unilever Tbk. Simultaneously, the Liquidity Ratio and Solvency Ratio do not have a significant effect on PT's Financial Performance. Unilever Tbk.